2015
DOI: 10.1093/jac/dku565
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation, D404N, in the connection subdomain of reverse transcriptase of HIV-1 CRF08_BC subtype confers cross-resistance to NNRTIs

Abstract: These results indicate that D404N is a novel NNRTI-associated mutation in the HIV-1 subtype CRF08_BC and provides information valuable for the monitoring of clinical RTI resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…14 In a later study, we demonstrated that D404N in the RT connection subdomain was an NNRTI resistance-related mutation that displayed cross-resistance to NVP, EFV, rilpivirine (RPV), and AZT. 16 In this study, we extended our research to the other two novel mutations, L228I and Y232H. Both these mutations locate in the b12-b13 hairpin of the palm subdomain, which contains the residues 227-235 (FLWMGYELH) and forms the so-called primer grip in RT.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…14 In a later study, we demonstrated that D404N in the RT connection subdomain was an NNRTI resistance-related mutation that displayed cross-resistance to NVP, EFV, rilpivirine (RPV), and AZT. 16 In this study, we extended our research to the other two novel mutations, L228I and Y232H. Both these mutations locate in the b12-b13 hairpin of the palm subdomain, which contains the residues 227-235 (FLWMGYELH) and forms the so-called primer grip in RT.…”
Section: Introductionmentioning
confidence: 92%
“…Six mutation patterns, including L228I, Y188C, Y188C/ L228I, A139V, Y232H, and A139V/Y232H, in RT were introduced into the pBRGX plasmid by site-directed mutagenesis as described previously. 16 Multiple mutations were introduced into pBRGX one by one. The presence of desired mutations in the plasmids was confirmed by DNA sequencing.…”
Section: Site-directed Mutagenesis and Virus Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultra-wide sequencing of the full-length viral genome, generating additional information on amino acid substitutions in Gag, Pol and Env, could enhance therapeutic outcome predictions [22][23][24][25][26][27].…”
Section: Ultra-wide Ngs For Genotypic Drug Resistance Testingmentioning
confidence: 99%
“…Unlike the marketed NNRTIs (Ren and Stammers 2008;Agneskog et al 2013;Sluis-Cremer 2014;Gallien et al 2015;Zhang et al 2015), W-1 exhibited more potent antiviral activity against NNRTIs-resistant HIV-1 strains (Lu et al 2007;Qin et al 2010). Therefore W-1 could have the potential to be next generation of drug candidate for treatment of acquired immunodeficiency syndrome (AIDS).…”
Section: Introductionmentioning
confidence: 99%